Underwriter Compensation and Corporate Monitoring. - Hansen, Robert S; Torregrosa, Paul (Journal of Finance, 1992)
Studies suggest that underwriting syndicates provide marketing services and certify the fairness of offer prices. The authors argue that syndicate lead banks also monitor manager effort, increasing the value of capital-raising companies. A given level of monitoring is associated with a given level of intrinsic value, so there is a "schedule" of certifiable offer prices, depending on the level of monitoring. Monitoring, marketing, and certification are, therefore, all legitimate syndicate functions. New evidence supporting the conclusion that syndicates provide corporate monitoring is presented.